Simplified Modular Access to Enantiopure 1,2-Aminoalcohols via Ni- Electrocatalytic Decarboxylative Arylation - Sun, Jiawei; Endo, Hirofumi; Emmanuel, Megan; Oderinde, Martins; Kawamata, Yu; baran, phil (ChemRxiv, 2023)
Chiral aminoalcohols are omnipresent in bioactive compounds. Conventional strategies to access this motif involve multiple-step reactions to install requisite functionalities stere- oselectively using conventional polar bond analysis. This study re- veals that a simple chiral oxazolidine-based carboxylic acid can be readily transformed to substituted chiral aminoalcohols with high stereochemical control by Ni-electrocatalytic decarboxylative ary- lation. This general, robust and scalable coupling can be used to synthesize variety of medicinally important compounds, avoiding protecting and functional group manipulations thereby dramati- cally simplifying their preparation.